Analysis of digestive tract content of the larvae of Polybia scutellaris (White) (Hymenoptera, Vespidae) - Fernandez Corujo, Victoria Lilian (2011)
Analysis of digestive tract content of the larvae of Polybia scutellaris (White) (Hymenoptera, Vespidae). Polybia scutellaris (White, 1841) is a social wasp of biological interest for its role as pollinator and maybe as biological control agent of sanitary and agricultural pests. This study examines the digestive tract contents of the larvae of P. scutellaris from four nests in Magdalena (Buenos Aires province, Argentina). Contents included both animal (arthropod parts) and plant (pollen, leaf and fruit epidermis) parts. The pollen content analysis showed that the wasps visited 19 different taxa of plants during the last active period of the colony before the nests had been collected. The range of sources used by P. scutellaris allows us characterizing the species as a generalist flower visitor. Wasps visited both native and exotic plants located nearby the nest. Most of the epidermal plant remains found in the larval digestive tract belonged to Malvaceae, a family not exploited by the studied colonies as pollen source.